EXPERIMENTAL STUDY ON THE INHIBITORY EFFECT OF SODIUM CANTHARIDINATE ON HUMAN HEPATOMA HEPG2 CELLS - Wen, Shi-Qi; Chen, Quan; Hu, Ming (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
Backgroud: Cantharidin, and its derivatives can not only inhibit the proliferation of tumor cells, but can also induce tumor cell apoptosis. It shows cantharidin exhibits a wide range of reactivity in anticancer. The objective of this paper was to study the inhibitory effect of sodium cantharidinate on human hepatoma HepG2 cells. Materials and Methods: MTT assay was used to detect the proliferation of HepG2 cells, and immunohisto-chemical method was used to detect the change in VEGF, protein level, and to determine the inhibitory effect of sodium cantharidinate on human hepatoma HepG2 cells. Results: As results, sodium cantharidinate significantly inhibited the growth of HepG2 cells in a time-and dose-dependent manner. Conclusion: We conclude that sodium cantharidinate has an inhibitory effect on human hepatoma HepG2 cells.